Pelatihan Manajemen Usaha Mikro melalui Strategi SWOT pada Koperasi Simpan Pinjam dan Pembiayaan Syariah di Kota Padang - Ilyas, Andre; Nofritar, Nofritar; Khairi, Awalul (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to enhance the capacity of KSPPS BMT Batuang Taba Nan XX in optimizing capital and micro-business management through the Strengths, Weaknesses, Opportunities, and Threats (SWOT) strategy. The implementation method of this community service utilized training and mentoring for 13 partners, culminating in assisting partners in formulating and selecting strategies using SWOT analysis techniques. The results of this community service showed that (1) there had been an improvement in partners’ understanding of the urgency of strategic development for cooperatives in the future. (2) successfully increased partners’ knowledge and competence in the fundamentals of cooperatives. (3) an increase in partners’ abilities and competencies in formulating cooperative development strategies, including successfully formulating a development strategy focused on KSPPS BMT Batuang Taba Nan XX.